Identification of Bacterial Cell Wall Lyases via Pseudo Amino Acid Composition. (29th June 2016) - Chen, Xin-Xin; Tang, Hua; Li, Wen-Chao; Wu, Hao; Chen, Wei; Ding, Hui; Lin, Hao
Abstract : Owing to the abuse of antibiotics, drug resistance of pathogenic bacteria becomes more and more serious. Therefore, it is interesting to develop a more reasonable way to solve this issue. Because they can destroy the bacterial cell structure and then kill the infectious bacterium, the bacterial cell wall lyases are suitable candidates of antibacteria sources. Thus, it is urgent to develop an accurate and efficient computational method to predict the lyases. Based on the consideration, in this paper, a set of objective and rigorous data was collected by searching through the Universal Protein Resource (the UniProt database), whereafter a feature selection technique based on the analysis of variance (ANOVA) was used to acquire optimal feature subset. Finally, the support vector machine (SVM) was used to perform prediction. The jackknife cross-validated results showed that the optimal average accuracy of 84.82% was achieved with the sensitivity of 76.47% and the specificity of 93.16%. For the convenience of other scholars, we built a free online server called Lypred . We believe that Lypred will become a practical tool for the research of cell wall lyases and development of antimicrobial agents.